2020
DOI: 10.20471/acc.2020.59.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Calcific Tendinopathy: Calcium Deposit Morphology Directly Affects Pain and Function of the Shoulder

Abstract: The aim of this study was to determine conventional ultrasonography characteristics of calcium deposits in patients diagnosed with calcific tendinopathy, to determine vascularization around deposits by power Doppler, and to compare morphological and power Doppler findings with clinical findings by use of two questionnaires. Pain and function were evaluated using the visual analog scale and two questionnaires, Constant Shoulder Score and Oxford Shoulder Score. All subjects underwent ultrasonography examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Recent studies have shown that the metaplasia mechanism of CaT is that tendon fibers transform into fibrocartilage and are calcified [ 14 ]. It has been reported in subsequent studies that metaplasia of tendon fibers, differentiation of tendon stem cells into chondrocytes and osteoblasts [ 15 ], endocrine disorders (thyroxine, estrogen, insulin) [ 16 ], and genetic factors [ 17 , 18 ] may also be related to the development of CaT. In this study, the incidence of diabetes and hypothyroidism was high, but this high incidence was not statistically significant in the two groups of patients.…”
Section: Discussioncontrasting
confidence: 49%
“…Recent studies have shown that the metaplasia mechanism of CaT is that tendon fibers transform into fibrocartilage and are calcified [ 14 ]. It has been reported in subsequent studies that metaplasia of tendon fibers, differentiation of tendon stem cells into chondrocytes and osteoblasts [ 15 ], endocrine disorders (thyroxine, estrogen, insulin) [ 16 ], and genetic factors [ 17 , 18 ] may also be related to the development of CaT. In this study, the incidence of diabetes and hypothyroidism was high, but this high incidence was not statistically significant in the two groups of patients.…”
Section: Discussioncontrasting
confidence: 49%
“…Calcific tendinopathy is easily diagnosed by using conventional radiography and ultrasound examination. Ultrasound examination is a fundamental tool for diagnosis and treatment, especially for determination of the localization, size, and morphology of the deposit [10]. Cesarec classified dividing deposits into three types using ultrasound: arch-shaped (1), cloudy (2), and fragmented and nodular (3).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the development of calcified deposits by Power Doppler as an indicator the inflammatory process in the tendon and an indicator of spontaneous resorption helps to predict the duration of the symptoms and to make a decision on the way of the treatment. Cesarec et al [10] postulated that by defining the stage of the calcific tendinopathy, we would be able to determine the mode of treatment and prognosis of the further course of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of distance, thickness or perimeter of a given structure were prevalent. In the study by Kim et www.fizjoterapiapolska.pl Some studies used the "Power Doppler" and "B" elastography modes [41,46]. In addition, other studies included measurements of thickness of the deltoid and pectoral muscles, as well as the coracoacromial ligament and the rotator cuff interval [27,33,39,48].…”
Section: Methods Of Measuring Internal Structures With Ultrasoundmentioning
confidence: 99%